Evaluation of the effectiveness of a serious game titled “Kookism” on the receptive lexicon in 4-9-year-old autistic children - Elham Hesami; Nour Mohammad Bakhshani; Maryam Arabpour Dahouie; Younes Zaheri (Heliyon)
Background: Autistic children often face difficulties with semantic skills such as receptive lexicon. Games based on behavioral principles have been emphasized for treating autistic children. Serious Games are a new and effective way to alleviate deficits in autistic children. Objectives: The present study aimed to design and investigate the efficiency of a Serious Game titled “Kookism” on the receptive lexicon of autistic children. Methods: The empirical study with a pretest-posttest design, and a two-months follow-up, involved 30 children (aged 4–9) at Birjand and Zahedan, Iran. The participants were selected by convenience sampling and randomly divided into experimental and control groups (each 15 participants). The control group received the Applied Behavior Analysis (ABA), while the experimental group received a treatment consisting of the ABA plus the “Kookism” game. The 20-min sessions were held every other day for two months. Data were collected using MacArthur-Bates Communicative Development Inventories. After confirming the essential assumptions for the covariance analysis, ANCOVA was used to analyze the data. Results: The findings showed a significant difference between the experimental and control groups in the increase in the participants’ receptive lexicon after eliminating the effects of the covariate (p < 0.05). Two months later, there was no statistically significant difference. (P = 0.144, F = 0.077, p > 0.05). Conclusions: The findings of this study indicate that Serious Games significantly improved the receptive lexicon of autistic children. This result remained for up to two months.